The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.3989/scimar.2007.71n1191
|View full text |Cite
|
Sign up to set email alerts
|

A new alien bryozoan <i>Celleporaria brunnea</i> (Hincks, 1884) in the Aegean Sea (eastern Mediterranean)

Abstract: SUMMARY: The ascophoran Bryozoa Celleporaria brunnea, a new record for the Mediterranean Sea, was found on Mytilus galloprovincialis collected in the inner part of Izmir Bay (Aegean Sea, Turkey) in September 2004. The species was previously reported from the Pacific coast of the United States. Its occurrence in the polluted inner part of Izmir Bay, near Alsancak Harbour, suggests that it has been newly introduced to the area, possibly via ship hulls. The morphological, ecological and zoogeographical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…Morphological characters described for our specimens, such as the colour of the colony, the suboral and interzooecial avicularia, the ooecium and the oral spines, are in accordance with the original descriptions of Hincks (1884) and the later ones of Hastings (1929), Osburn (1952), Soule (1961, Soule and Soule (1964), Soule et al (1995), Koçak (2007), Seo andMin (2009), Canning-Clode et al (2013) and Harmelin (2014). Despite these morphological similarities, a comparison between our morphometric measurements and literature data has highlighted some differences.…”
Section: Systematicssupporting
confidence: 57%
See 4 more Smart Citations
“…Morphological characters described for our specimens, such as the colour of the colony, the suboral and interzooecial avicularia, the ooecium and the oral spines, are in accordance with the original descriptions of Hincks (1884) and the later ones of Hastings (1929), Osburn (1952), Soule (1961, Soule and Soule (1964), Soule et al (1995), Koçak (2007), Seo andMin (2009), Canning-Clode et al (2013) and Harmelin (2014). Despite these morphological similarities, a comparison between our morphometric measurements and literature data has highlighted some differences.…”
Section: Systematicssupporting
confidence: 57%
“…Orifice measurements are mostly in accordance with those previously reported for H. brunnea material from Ecuador (Osburn 1952). On the other hand, orifice measurements of our specimens are different to those of Koçak (2007), Canning-Clode et al (2013) and Harmelin (2014). Koçak (2007) described the orifice as clearly broader than long, Canning-Clode et al (2013) reported an orifice that is bigger in size in both length and width and Harmelin (2014) reported similar values for both length and width, with just a slightly longer orifice on average.…”
Section: Systematicsmentioning
confidence: 40%
See 3 more Smart Citations